Expanding the genotypic spectrum of CCBE1 mutations in Hennekam syndrome. Issue 10 (27th June 2016) - Crawford, Joanna; Bower, Neil I.; Hogan, Benjamin M.; Taft, Ryan J.; Gabbett, Michael T.; McGaughran, Julie; Simons, Cas
Abstract : Hennekam lymphangiectasia–lymphedema syndrome is an autosomal recessive disorder, with 25% of patients having mutations in CCBE1 . We identified a family with two brothers presenting with primary lymphedema, and performed exome sequencing to determine the cause of their disease. Analysis of four family members showed that both affected brothers had the same rare compound heterozygous mutations in CCBE1 . The presumed paternally inherited NM_133459.3:c.310G>A; p.(Asp104Asn), lies adjacent to other known pathogenic CCBE1 mutations, while the maternally inherited NM_133459.3:c.80T>C; p.(Leu27Pro) lies in the CCBE1 signal peptide, which has not previously been associated with disease. Functional analysis in a zebrafish model of lymphatic disease showed that both mutations lead to CCBE1 loss of function, confirming the pathogenicity of these variants and expanding the genotypic spectrum of lymphatic disorders. © 2016 Wiley Periodicals, Inc.